The Effects of Compound 48/80 on the Fibrinolytic Activity of Dogs - Eyüboğlu, Hughette; Akcasu, Alâeddin (Thrombosis and Haemostasis, 1979)
It has been demonstrated that histamine by itself, did play some role in the activation mechanism of fibrinolysis. In this particular work, it was demonstrated that histamine at doses not affecting blood pressure levels, did not exert any direct immediate effect on fibrinolytic activity.Compound 48/80, a powerful mast cell depleter and histamine liberator, by itself, has no direct molecular effect on fibrinolytic activity, but rather, through the release of activators and/or inhibitors form mast cells, will exert either an activating or inhibiting action, according to the dose used. Low doses, such as 0.2 mg/kg i. v. will achieve a higher degree of activator release, while doses of 1.0 mg/kg will result in higher inhibitors release from mast cells.